2024
DOI: 10.1186/s12951-024-02310-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate coating enhances osteointegration of melt electrowritten scaffold by regulating macrophage polarization

Yubo Shi,
Weidong Tao,
Wenjing Yang
et al.

Abstract: The osteoimmune microenvironment induced by implants plays a significant role in bone regeneration. It is essential to efficiently and timely switch the macrophage phenotype from M1 to M2 for optimal bone healing. This study examined the impact of a calcium phosphate (CaP) coating on the physiochemical properties of highly ordered polycaprolactone (PCL) scaffolds fabricated using melt electrowritten (MEW). Additionally, it investigated the influence of these scaffolds on macrophage polarization and their immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…These factors may have activated the PI3K/AKT and cAMP-PKA pathways, promoting macrophage M2 polarization. 44 Research by Sun et al identified a calcium phosphate-mediated environment rich in PO 4 3− . Extracellular PO 4 3− is transported into the cytoplasm via the sodium-dependent phosphate transporter 1, participating in the tricarboxylic acid cycle and oxidative phosphorylation to generate energy in the form of ATP.…”
Section: Resultsmentioning
confidence: 99%
“…These factors may have activated the PI3K/AKT and cAMP-PKA pathways, promoting macrophage M2 polarization. 44 Research by Sun et al identified a calcium phosphate-mediated environment rich in PO 4 3− . Extracellular PO 4 3− is transported into the cytoplasm via the sodium-dependent phosphate transporter 1, participating in the tricarboxylic acid cycle and oxidative phosphorylation to generate energy in the form of ATP.…”
Section: Resultsmentioning
confidence: 99%